Neuroaccouting as a Modern Approach to Accounting - Miązek , Amadeusz (Studia Oeconomica Posnaniensia, 2014)
The article describes neuroaccounting as a new approach to behavioural research in accounting. The first section describes the essence of the term together with the reasons for the use of neurobiological research in economics. Technical details are reduced to an absolute minimum, and the methods of measurement are delineated to better present the possibilities. In the next section neuroaccounting is included under behavioral accounting, and the last section presents critical opinions relating to the terms neuroaccounting and neuroeconomics found in world literature.